2012
DOI: 10.1103/physrevb.85.224406
|View full text |Cite
|
Sign up to set email alerts
|

Interface atomic structures and magnetic anisotropy of Fe and Pd/Fe monatomic films on Pd(001)

Abstract: The magnetic anisotropy of monatomic Fe films on Pd(001) with or without a Pd overlayer was investigated from the standpoint of interface atomic structures. Quantitative analysis included low-energy electron diffraction and x-ray magnetic circular dichroism (XMCD) experiments, and first-principles calculations were also performed on monatomic Fe and Pd/Fe systems. It was revealed that Fe atoms intermix with the Pd substrate at room temperature. A spin reorientation transition occurs at a critical Fe thickness … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
6
1

Year Published

2013
2013
2020
2020

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(7 citation statements)
references
References 47 publications
0
6
1
Order By: Relevance
“…The decrease in the measured Fe magnetization would therefore indicate an increase in the anisotropy away from the field, presumably into the out-of-plane direction. However, previous works have reported that the Pd/Fe system at room temperature has a dominant in-plane anisotropy for all thicknesses [41], while other works performed at low-temperatures have reported that the out-of-plane anisotropy decreases with increasing thickness of the Pd capping layer [42]. Based on these results, the measured projection of the magnetization should increase with Pd thickness, contrary to our observations.…”
Section: Resultscontrasting
confidence: 99%
See 1 more Smart Citation
“…The decrease in the measured Fe magnetization would therefore indicate an increase in the anisotropy away from the field, presumably into the out-of-plane direction. However, previous works have reported that the Pd/Fe system at room temperature has a dominant in-plane anisotropy for all thicknesses [41], while other works performed at low-temperatures have reported that the out-of-plane anisotropy decreases with increasing thickness of the Pd capping layer [42]. Based on these results, the measured projection of the magnetization should increase with Pd thickness, contrary to our observations.…”
Section: Resultscontrasting
confidence: 99%
“…Growing the Pd capping layer by room-temperature sputtering, rather than e. g. e-beam evaporation [42], results in initial island growth with increasing coalescence as more Pd is deposited. The increasing contact area between the Pd and Fe may change the magnetization.…”
Section: Structural Evolution Of the Sample During Growthmentioning
confidence: 99%
“…Ultrathin Co/Pd multilayers are one of such representative artificial nanomaterials that exhibit interface perpendicular magnetic anisotropy (PMA), and the development of artificially synthesised PMA has led researchers to the expectation of ultra-high density recording media [2,3]. Since then, extensive efforts have been made for studying electronic and spin structures of the interfaces of ultra-thin magnetic multilayers [4][5][6][7][8][9][10][11][12] and nanostructures [13][14][15][16]. Studies on Co atoms performed using x-ray magnetic circular dichroism (XMCD) have suggested the enhancement of orbital magnetic moments at the interfacial Co that is adjacent to Pd or Pt.…”
mentioning
confidence: 99%
“…Studies on Co atoms performed using x-ray magnetic circular dichroism (XMCD) have suggested the enhancement of orbital magnetic moments at the interfacial Co that is adjacent to Pd or Pt. It has been reported that the PMA emerges due to the cooperative effects between spin moments in 3d TMs and large spin-orbit interactions ξLS in the non-magnetic 4d or 5d TMs, where ξ is the spin-orbit coupling constants, L is orbital angular momentum, and S is the spin angular momentum [4][5][6][7][8][9][10][11][12][13][14][15][16]. The Co/Pd interfaces and multilayers have also been employed to demonstrate the photo-induced precession of magnetisation [17,18], the creation of skyrmions using the interfacial Dzyaloshinskii-Moriya interaction [19], and magnetisation reversal using the spin-orbit torque phenomena [20].…”
mentioning
confidence: 99%
“…To fully capture these effects, which underpin much of current spintronics research, calls for both static and dynamic calculations of the magnetic moments and their interactions to be performed. Currently, there are no analytical solutions available for describing the changes in the induced magnetization with temperature in technologically relevant thin film heterostructures; with results from computational models at fixed temperature only in their infancy 30 . Finally, we have shown that if the spatially integrated induced moment in a material contributes significantly to the total magnetization of a sample, measurements of M (T ) may yield exponents for the overall magnetic phase transition that can be misinterpreted.…”
Section: Discussionmentioning
confidence: 99%